Clinico-demographic and microbiological profile of acute pyelonephritis in Azadi Teaching Hospital, Duhok province, Iraqi Kurdistan - Taha, Sagvan Kareem; Abd, Kais Hasan; Abdulkareem, Fatima Nawaf; Saleem, Zana Sidiq Mohammaed; Almukhtar, Safa EizAldein; Merza, Muayad A (Asian Journal of Medical and Biological Research, 2023)
The aims of this study were to identify the demographic and clinical characteristics of community associated acute pyelonephritis (CA-APN) or healthcare associated APN (HCA-APN), to determine risk factors linked with APN, and to identify the microbiological profile and its susceptibility patterns to antibiotics. A cross-sectional study was conducted from September to November 2022 at the nephrology unit of Azadi Teaching Hospital, Duhok, Iraqi Kurdistan. Urine and blood samples were collected from patients diagnosed with APN. These samples were investigated to identify the microbiologic profile of the infecting organisms and determine their antibiotic susceptibility results. From a total of 97 adult and elderly APN patients, 55 (56.7%) were classified as HCA-APN, while 42 (43.3%) were classified as CA-APN. In the univariate analysis, age ≥ 65, catheterization, chronic kidney disease, hemodialysis, diabetes mellitus (DM), cardiovascular disease (CVD), neurologic disease, chronic pulmonary disease, PCT level, and ANC were identified as significant risk factors for HCA-APN compared to CA-APN. Patients with catheterization and CVD history showed independent association in the multivariate analysis. The overall mortality rate was 11.3%, which was significantly associated with HCA-APN (P = 0.002). Considering the microbiological profile, Escherichia coli uropathogen (n=61) was the predominant isolated bacteria followed by Klebsiella pneumoniae (n=17). High antibiotic resistance rates were observed in fluoroquinolones and third generation cephalosporin classes among E. coli uropathogen in both CA-APN and HCA-APN patients, with a rate of 74.5 % and 63.9%, respectively. In conclusion, there is an increase in mortality rate regarding HCA-APN. The HCA-APN characteristics should be considered when prescribing empiric antibiotics. In our local setting, carbapenems are effective empiric therapies against enterobacteraceae uropathogens, for both HCA-APN and CA-APN. In order to prevent the emergence and spread of antibiotic resistance, implementing surveillance systems, infection prevention and control measures, and antimicrobial stewardship programs within our healthcare setting is crucial. Asian J. Med. Biol. Res. 2023, 9 (3), 59-69